Role of Harmonization and Unification in Perspective of China–Pakistan Economic Corridor Physical Infrastructure and Applicable Laws - IDREES, Rao Qasim; CHEEMA, Zaheer Iqbal; RIAZ, Jawad (Journal of Advanced Research in Law and Economics, 2020)
This research paper centers on logistics investment policies both in legal and social manners for current and future China Pakistan trade with reference to CPEC. With further improvement, many other regional economic players in prospective time may join the CPEC projects, where Afghanistan, Central Asian and SAARC states are prominent to enter for the said purpose. There are different practices around the world to achieve socio economic progress. Hence a unified and harmonized system of applicable rules and regulation is required forthwith in order to get benefits from CPEC. This research paper primarily deals with the history of China Pakistan relations in the context of CPEC and Belt and Road Initiative and their benefits to Pakistan. Furthermore, the role of harmonization and unification among legal rules and physical infrastructure is discussed to find benefits and better solutions.  This study applies legal research process where historical method is conducted to observe the history of Belt and Road Initiative (BRI) which further includes China Pakistan trade relations and their situation regarding logistics investment in CPEC. Furthermore, comparative legal research is applied to find out the differences among Pakistan legal system and international laws to make foreign investment more beneficial. This research concludes that domestic legislation in Pakistan in the areas of logistics and transportation is very limited in scope. Furthermore, such legislation does not cover the broad area of international trade. In current situation it is pertinent for Pakistan to introduce and revise such legislations and codes and not doing so China may again ask Pakistan to enact law as per his own benefits which he did while Pakistan amend Competition and special economic zone laws. Furthermore, CPEC in future will invite many other trade partners for their investment contribution in the region. This necessitates Pakistan to build strong physical infrastructure and negotiate further trade agreements and relevant legislation with other partners in the region and not only rely upon bilateral agreements with China.